Identification of OTUD6B as a new biomarker for prognosis and immunotherapy by pan-cancer analysis - Zhao, Guang; Song, Dingli; Wu, Jie; Yang, Sanhu; Shi, Sien; Cui, Xiaohai; Ren, Hong; Zhang, Boxiang (Frontiers in Immunology, 2022)
Background: Ovarian-tumor (OTU) domain-containing protein 6B (OTUD6B), one of newly identified OTU deubiquitinating enzyme family, is proved to be associated with tumor progression. However, whether it plays a key role in pan-cancer still remains unknown. Methods: The proﬁles of OTUD6B expression in multiple cancers were analyzed using The Cancer Genome Atlas (TCGA) database. Information of protein expression was performed based on HPA, GeneCards, and String database. K-M plotter and survival data analysis were used to analyze prognostic value of OTUD6B expression, including overall survival (OS), disease-speciﬁc survival (DSS), disease-free interval (DFI), and progression-free interval (PFI). R package “clusterProfiler” was used for enrichment analysis of OTUD6B. Furthermore, we analyzed the correlation between the expression of OTUD6B, immune infiltration and immune-related genes. Additionally, we preliminarily validated the its tumorigenic effect in lung cancer cell lines. Findings: OTUD6B expression was unregulated in most cancers, such as COAD, CHOL, and LUAD, and predicted poor prognosis in most cancers in TCGA. Results showed that OTUD6B expression was positively correlated with memory CD4+ T cells, Th1 CD4+ T cells and CD8+ T cells. In terms of the immune related genes, OTUD6B was found to be associated with most types of genes, such as immunostimulatory genes KDR, TGFBR1 and IL-10. Moreover, for most type of tumors, immune score was found to be negatively correlated with OTUD6B expression. In addition, lung cancer cell lines with OTUD6B knockdown significantly inhibited proliferation and invasion ability of lung cancer cells. Conclusions: The study indicated OTUD6B is an oncogene and may serve as a new potential biomarker in various tumors. OTUD6B may play a part in TIME, which could be applied as a new target for cancer therapy.